2021
DOI: 10.1200/jco.2021.39.3_suppl.218
|View full text |Cite
|
Sign up to set email alerts
|

A multi-institutional phase Ib/II trial of first-line triplet regimen (Pembrolizumab, Trastuzumab, Chemotherapy) for HER2-positive advanced gastric and gastroesophageal junction cancer (PANTHERA Trial): Molecular profiling and clinical update.

Abstract: 218 Background: We report the updated clinical data and molecular profiling results of a multi-institutional phase Ib/II trial of triple combination (pembrolizumab, trastuzumab, and chempotherapy) as first line therapy for HER2 positive advanced gastric and gastroesophageal junction (AGC/GEJ) cancer. (PANTHERA trial; NCT02901301). Methods: Pembrolizumab 200mg IV D1, Trastuzumab 6mg/kg (after 8mg/kg load) D1, Capecitabine 1000mg/m2 bid D1-14, and Cisplatin 80mg/m2 D1 every 3 weeks was selected as recommended p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 0 publications
4
32
0
2
Order By: Relevance
“…Furthermore, the interim results of the PANTHERA trial reported the exploratory analysis of TMB in patients who received first line pembrolizumab plus chemotherapy with trastuzumab for HER-2-positive GEC. In this analysis, high TMB was associated with a nonsignificant tendency towards increased mPFS (22.0 vs. 8.6 months, p = 0.2835) [35]. These results suggest that TMB appears to have a potential as a biomarker of response to anti-PD-1 therapy in GEC.…”
Section: Tumor Mutational Burdenmentioning
confidence: 59%
See 1 more Smart Citation
“…Furthermore, the interim results of the PANTHERA trial reported the exploratory analysis of TMB in patients who received first line pembrolizumab plus chemotherapy with trastuzumab for HER-2-positive GEC. In this analysis, high TMB was associated with a nonsignificant tendency towards increased mPFS (22.0 vs. 8.6 months, p = 0.2835) [35]. These results suggest that TMB appears to have a potential as a biomarker of response to anti-PD-1 therapy in GEC.…”
Section: Tumor Mutational Burdenmentioning
confidence: 59%
“…The study demonstrated a six-month PFS of 70% (26/37), meeting its primary endpoint [34]. Additionally, a multicenter, single-arm phase Ib/II PANTHERA trial conducted in Korea recently reported in GI-ASCO 2021 a promising ORR of 76.7%, mPFS of 8.6 months, mOS of 19.3 months, and DOR of 10.8 months [35]. Based on these results, the KEYNOTE-811 trial is currently under way, comparing the addition of pembrolizumab versus placebo to trastuzumab and chemotherapy in untreated, HER-2 positive advanced GEC (NCT03615326).…”
Section: Immunotherapy Trials In Gastroesophageal Cancermentioning
confidence: 85%
“…79 In the phase 1b/2 PANTHERA trial (NCT02901301), first-line triple therapy with pembrolizumab, trastuzumab and chemotherapy showed promising efficacy in the treatment of advanced HER2 amplified gastric cancer regardless of PD-L1 status. 80 The ORR was 77%, and patients with HER2 amplification per NGS (≥ 4 copy number) had a statistically significantly longer median PFS than those without HER2 amplification (median PFS, 22.0 months vs 7.7 months; P =0.03). The same trend was shown in patients with altered RTK/RAS pathways compared with wild-type RTK/RAS (median PFS, 13.8 months vs 4.9 months; P = 0.001).…”
Section: Dovepressmentioning
confidence: 91%
“…Together with trastuzumab deruxtecan and margetuximab, zanidatamab appears to be a good candidate for integration with chemotherapy or immunotherapy in future for HER2 positive gastric cancer patients [5,6]. Considering HER2directed therapy plus immunotherapy, the results of triplet treatment of chemotherapy, trastuzumab and pembrolizumab in first-line advanced gastric cancer in the PANTERA study were also presented at ASCO-GI 2021 [7]. Radiological response rates of 76% were observed, with encouraging median OS of 19.3 months (95% CI, 16.5-NR).…”
Section: Highlights In Oesophagogastric Cancer Eortc Oesophagogastric Task Force: Elizabeth Smyth and Dorothea Wagnermentioning
confidence: 99%